Surf zone Pam Withers (North Vancouver, B.C. : Walrus Books, 2005)
A scuba-diving accident leaves Jake and Peter and a surfer girl stranded on a deserted island with surfboards as their only means of escape. The storm of the century is fast approaching and they need to think fast if they're going to get home in one piece.
Keywords: Surfing -- Juvenile fiction; Deep diving -- Juvenile fiction; Wilderness survival -- Juvenile fiction